373 ESOPHAGEAL BODY PERISTALSIS IN PATIENTS WITH NORMAL LOWER ESOPHAGEAL SPHINCTER: ARE VIDEO ESOPHAGOGRAM AND HIGH-RESOLUTION MANOMETRY IN AGREEMENT?. (14th September 2020) - Razia, D; Giulini, L; Bremner, R; Mittal, S
Abstract:  : Peristaltic disorders of the esophageal body have been categorized according to how they appear on high-resolution manometry. Abnormalities in peristalsis may lead to abnormal esophageal clearance and dysphagia. The aim of our retrospective analysis was to study bolus transit patterns on barium esophagogram in patients with various grades of esophageal body peristalsis as diagnosed by high-resolution manometry. Methods: After Institutional Review Board approval, we queried an esophageal center database to identify patients with normal lower esophageal sphincter parameters. Patients with jackhammer esophagus, esophageal spasm, previous foregut surgery, hiatal hernia, and fragmented peristalsis were excluded. Remaining patients were divided into 11 groups based on their percentages of normal swallows out of 10 swallows (0%–100% swallows normal, DCI > 450 mmHg.s.cm ). All previously obtained video esophagograms were re-evaluated in blinded fashion. Bolus transit time through the esophagus was measured in upright and prone positions, using live time stamps at the entry and exit of the bolus. ANOVA and χ2 were used. Results: In total, 146 patients were included in the analysis. 73 (50%) were men. Mean age and body mass index were 58.4 ± 14.7 years and 22.8 ± 10.4 kg/m2, respectively. Bolus transit time in prone-position swallows increased in tandem with increases in number of abnormal swallows (11.3 ± 3.7, 22 ± 15.5, 29.5 ± 24.3, 42.7 ± 39.5, 42.4 ± 46.9, 64 ± 70.8, 59.4 ± 34.6, 58.8 ± 37.9, 110 ± 66.6, 83.2 ± 49.6 and 105.6 ± 72.5 seconds, p < 0.0001) but no difference was noted in upright-position bolus transit time (p = 0.317). There was a dropoff in level of significance at Group 5 (60% swallows normal) compared to Group 11 (absent contractility), after which there were no inter-group differences (Fig. 1). Conclusion: Bolus transit time in prone-position swallows progressively increases as percentage of normal swallows decreases. Further work associated with symptoms to define a cutoff between normal and ineffective peristalsis would be useful.